The Development of Reading Materials Based on Moluccan Folklores for Senior High School Students at Grade Tenth of SMA Negeri 2 Ambon - Meyer, Fredi (Honoli of Journal Primary Teacher Education, 2021)
Lack of students’ understanding influences their activities in the classroom activity. The purpose of the research was to develop Reading material based on Moluccan Folklore for grade Tenth of SMA Negeri 2 Ambon which was derived from research questions: 1). What are the learning needs of Maluku Folklore materials for tenth graders of SMA Negeri 2 Ambon?. 2). How is the design of Maluku Folklore materials for tenth graders of SMA Negeri 2 Ambon. 3).How is the effectiveness of Maluku Folklore materials for tenth graders of SMA Negeri 2 Ambon? The research used Research and Development (R & D) with ADDIE model. There are 35 students as sample at grade tenth of SMA Negeri 2 Ambon. There are analysis, design, develop material, validation, and revision in thisphase. The collection of the data used questioner, and test. The research developed five units in the reading material based on Mollucan Folklore on Curriculum 2013. The result of the product validation was 3,61. It was categorized as “very good”. Meanwhile, the result of the post test was 81,5 and it was categorized as “good”.